(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Searching for the human being’s grounding, Desanka Maksimović has connected religious, historical, lyrical and metahysical concepts in her collection of poems I Seek Clemency. As an artist, she has testified that men, sinful or sinless, have to be merciful, since mercy represents the very base of their human identity.